Adult hippocampal neurogenesis in Parkinson's disease: impact on neuronal survival and plasticity - Regensburger, Martin; Prots, Iryna; Winner, Beate (Neural Plasticity, 2014)
In Parkinson's disease (PD) and other synucleinopathies, chronic neurodegeneration occurs within different areas of the central nervous system leading to progressive motor and nonmotor symptoms. The symptomatic treatment options that are currently available do not slow or halt disease progression. This highlights the need of a better understanding of disease mechanisms and disease models. The generation of newborn neurons in the adult hippocampus and in the subventricular zone/olfactory bulb system is affected by many different regulators and possibly involved in memory processing, depression, and olfaction, symptoms which commonly occur in PD. The pathology of the adult neurogenic niches in human PD patients is still mostly elusive, but different preclinical models have shown profound alterations of adult neurogenesis. Alterations in stem cell proliferation, differentiation, and survival as well as neurite outgrowth and spine formation have been related to different aspects in PD pathogenesis. Therefore, neurogenesis in the adult brain provides an ideal model to study disease mechanisms and compounds. In addition, adult newborn neurons have been proposed as a source of endogenous repair. Herein, we review current knowledge about the adult neurogenic niches in PD and highlight areas of future research.
EVALuna2:26222

Alpha-synuclein fine-tunes neuronal response to pro-inflammatory cytokines - Sigutova, Veronika; Xiang, Wei; Regensburger, Martin; Winner, Beate; Prots, Iryna (Brain Behavior and Immunity, 2024)
Pro-inflammatory cytokines are emerging as neuroinflammatory mediators in Parkinson's disease (PD) due to their ability to act through neuronal cytokine receptors. Critical questions persist regarding the role of cytokines in neuronal dysfunction and their contribution to PD pathology. Specifically, the potential synergy of the hallmark PD protein alpha-synuclein (α-syn) with cytokines is of interest. We therefore investigated the direct impact of pro-inflammatory cytokines on neurons and hypothesized that α-syn pathology exacerbates cytokine-induced neuronal deficits in PD. iPSC-derived cortical neurons (CNs) from healthy controls and patients with α-syn gene locus duplication (SNCA dupl) were stimulated with IL-17A, TNF-α, IFN-γ, or a combination thereof. For rescue experiments, CNs were pre-treated with α-syn anti-oligomerisation compound NPT100-18A prior to IL-17A stimulation. Cytokine receptor expression, microtubule cytoskeleton, axonal transport and neuronal activity were assessed. SNCA dupl CNs displayed an increased IL-17A receptor expression and impaired IL-17A-mediated cytokine receptor regulation. Cytokines exacerbated the altered distribution of tubulin post-translational modifications in SNCA dupl neurites, with SNCA dupl-specific IL-17A effects. Tau pathology in SNCA dupl CNs was also aggravated by IL-17A and cytokine mix. Cytokines slowed down mitochondrial axonal transport, with IL-17A-mediated retrograde slowing in SNCA dupl only. The pre-treatment of SNCA dupl CNs with NPT100-18A prevented the IL-17A-induced functional impairments in axonal transport and neural activity. Our work elucidates the detrimental effects of pro-inflammatory cytokines, particularly IL-17A, on human neuronal structure and function in the context of α-syn pathology, suggesting that cytokine-mediated inflammation represents a second hit to neurons in PD which is amenable to disease modifying therapies that are currently in clinical trials.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Alpha-synuclein; Cytokines; Neuroinflammation; Parkinson's disease

Alpha-synuclein prevents the formation of spherical mitochondria and apoptosis under oxidative stress - Winner, Beate; Menges, Stefanie; Minakaki, Georgia; Schaefer, Patrick; Meixner, Holger; Prots, Iryna; Schlötzer-Schrehardt, Ursula; Friedland, Kristina; Outeiro, Tiago F.; Winklhofer, Konstanze F.; Von Arnim, Christine A. F.; Xiang, Wei; et al. (Scientific Reports, 2017)
Oxidative stress (OS), mitochondrial dysfunction, and dysregulation of alpha-synuclein (aSyn) homeostasis are key pathogenic factors in Parkinson's disease. Nevertheless, the role of aSyn in mitochondrial physiology remains elusive. Thus, we addressed the impact of aSyn specifically on mitochondrial response to OS in neural cells. We characterize a distinct type of mitochondrial fragmentation, following H2O2 or 6-OHDA-induced OS, defined by spherically-shaped and hyperpolarized mitochondria, termed "mitospheres". Mitosphere formation mechanistically depended on the fission factor Drp1, and was paralleled by reduced mitochondrial fusion. Furthermore, mitospheres were linked to a decrease in mitochondrial activity, and preceded Caspase3 activation. Even though fragmentation of dysfunctional mitochondria is considered to be a prerequisite for mitochondrial degradation, mitospheres were not degraded via Parkin-mediated mitophagy. Importantly, we provide compelling evidence that aSyn prevents mitosphere formation and reduces apoptosis under OS. In contrast, aSyn did not protect against Rotenone, which led to a different, previously described donut-shaped mitochondrial morphology. Our findings reveal a dichotomic role of aSyn in mitochondrial biology, which is linked to distinct types of stress-induced mitochondrial fragmentation. Specifically, aSyn may be part of a cellular defense mechanism preserving neural mitochondrial homeostasis in the presence of increased OS levels, while not protecting against stressors directly affecting mitochondrial function.

A monocyte gene expression signature in the early clinical course of Parkinson's disease - Schlachetzki, Johannes; Prots, Iryna; Tao, Jenhan; Chun, Hyun B.; Saijo, Kaoru; Gosselin, David; Winner, Beate; Glass, Christopher K.; Winkler, Jürgen (Scientific Reports, 2018)
Microglia are the main immune cells of the brain and express a large genetic pattern of genes linked to Parkinson's disease risk alleles. Monocytes like microglia are myeloid-lineage cells, raising the questions of the extent to which they share gene expression with microglia and whether they are already altered early in the clinical course of the disease. To decipher a monocytic gene expression signature in Parkinson's disease, we performed RNA-seq and applied the two-sample Kolmogorov-Smirnov test to identify differentially expressed genes between controls and patients with Parkinson's disease and changes in gene expression variability and dysregulation. The gene expression profiles of normal human monocytes and microglia showed a plethora of differentially expressed genes. Additionally, we identified a distinct gene expression pattern of monocytes isolated from Parkinson's disease patients at an early disease stage compared to controls using the Kolmogorov-Smirnov test. Differentially expressed genes included genes involved in immune activation such as HLA-DQB1, MYD88, REL, and TNF-alpha. Our data suggest that future studies of distinct leukocyte subsets are warranted to identify possible surrogate biomarkers and may lead to the identification of novel interventions early in the disease course.
EVALuna2:35780

A monocyte gene expression signature in the early clinical course of Parkinson's disease (vol 8, 10757, 2018) - Winner, Beate; Schlachetzki, Johannes C.M.; Prots, Iryna; Tao, Jenhan; Chun, Hyun B.; Saijo, Kaoru; Gosselin, David; Glass, Christopher K.; Winkler, Jürgen (Scientific Reports, 2020)

An Enhanced Retroviral Vector for Efficient Genetic Manipulation and Selection in Mammalian Cells - Triller, Jana; Prots, Iryna; Jäck, Hans Martin; Wittmann, Jürgen (Biomolecules, 2024)
Introducing genetic material into hard-to-transfect mammalian cell lines and primary cells is often best achieved through retroviral infection. An ideal retroviral vector should offer a compact, selectable, and screenable marker while maximizing transgene delivery capacity. However, a previously published retroviral vector featuring an EGFP/Puromycin fusion protein failed to meet these criteria in our experiments. We encountered issues such as low infection efficiency, weak EGFP fluorescence, and selection against infected cells. To address these shortcomings, we developed a novel retroviral vector based on the Moloney murine leukemia virus. This vector includes a compact bifunctional EGFP and Puromycin resistance cassette connected by a 2A peptide. Our extensively tested vector demonstrated superior EGFP expression, efficient Puromycin selection, and no growth penalty in infected cells compared with the earlier design. These benefits were consistent across multiple mammalian cell types, underscoring the versatility of our vector. In summary, our enhanced retroviral vector offers a robust solution for efficient infection, reliable detection, and effective selection in mammalian cells. Its improved performance and compact design make it an ideal choice for a wide range of applications involving precise genetic manipulation and characterization in cell-based studies.
CRIS-Team Scopus Importer:2024-10-04
Keywords: B cells; EGFP; FACS; fusion protein; infection; linker; Puromycin; retrovirus; T2A

Author Correction: A monocyte gene expression signature in the early clinical course of Parkinson’s disease (Scientific Reports, (2018), 8, 1, (10757), 10.1038/s41598-018-28986-7) - Schlachetzki, Johannes; Prots, Iryna; Tao, Jenhan; Chun, Hyun B.; Saijo, Kaoru; Gosselin, David; Winner, Beate; Glass, Christopher K.; Winkler, Jürgen (Scientific Reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.
CRIS-Team Scopus Importer:2020-04-17

Axon-Specific Mitochondrial Pathology in SPG11 Alpha Motor Neurons - Güner, Fabian; Pozner, Tatyana; Krach, Florian; Prots, Iryna; Loskarn, Sandra; Schlötzer-Schrehardt, Ursula; Winkler, Jürgen; Winner, Beate; Regensburger, Martin (Frontiers in Neuroscience, 2021)
Pathogenic variants in SPG11 are the most frequent cause of autosomal recessive complicated hereditary spastic paraplegia (HSP). In addition to spastic paraplegia caused by corticospinal degeneration, most patients are significantly affected by progressive weakness and muscle wasting due to alpha motor neuron (MN) degeneration. Mitochondria play a crucial role in neuronal health, and mitochondrial deficits were reported in other types of HSPs. To investigate whether mitochondrial pathology is present in SPG11, we differentiated MNs from induced pluripotent stem cells derived from SPG11 patients and controls. MN derived from human embryonic stem cells and an isogenic SPG11 knockout line were also included in the study. Morphological analysis of mitochondria in the MN soma versus neurites revealed specific alterations of mitochondrial morphology within SPG11 neurites, but not within the soma. In addition, impaired mitochondrial membrane potential was indicative of mitochondrial dysfunction. Moreover, we reveal neuritic aggregates further supporting neurite pathology in SPG11. Correspondingly, using a microfluidic-based MN culture system, we demonstrate that axonal mitochondrial transport was significantly impaired in SPG11. Overall, our data demonstrate that alterations in morphology, function, and transport of mitochondria are an important feature of axonal dysfunction in SPG11 MNs.
CRIS-Team Scopus Importer:2021-08-06
Keywords: SPG11; alpha motor neuron; axonal transport; hereditary spastic paraplegia; induced pluripotent stem cells; mitochondria

Demonstration of brain region-specific neuronal vulnerability in human iPSC-based model of familial Parkinson's disease - Brazdis, Razvan Marius; Alecu, Julian E.; Marsch, Daniel; Dahms, Annika; Simmnacher, Katrin; Lörentz, Sandra; Brendler, Anna; Schneider, Yanni; Marxreiter, Franz; Roybon, Laurent; Winner, Beate; Xiang, Wei; et al. (Human Molecular Genetics, 2020)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by protein inclusions mostly composed of aggregated forms of α-synuclein (α-Syn) and by the progressive degeneration of midbrain dopaminergic neurons (mDANs), resulting in motor symptoms. While other brain regions also undergo pathologic changes in PD, the relevance of α-Syn aggregation for the preferential loss of mDANs in PD pathology is not completely understood yet. To elucidate the mechanisms of the brain region-specific neuronal vulnerability in PD, we modeled human PD using human-induced pluripotent stem cells (iPSCs) from familial PD cases with a duplication (Dupl) of the α-Syn gene (SNCA) locus. Human iPSCs from PD Dupl patients and a control individual were differentiated into mDANs and cortical projection neurons (CPNs). SNCA dosage increase did not influence the differentiation efficiency of mDANs and CPNs. However, elevated α-Syn pathology, as revealed by enhanced α-Syn insolubility and phosphorylation, was determined in PD-derived mDANs compared with PD CPNs. PD-derived mDANs exhibited higher levels of reactive oxygen species and protein nitration levels compared with CPNs, which might underlie elevated α-Syn pathology observed in mDANs. Finally, increased neuronal death was observed in PD-derived mDANs compared to PD CPNs and to control mDANs and CPNs. Our results reveal, for the first time, a higher α-Syn pathology, oxidative stress level, and neuronal death rate in human PD mDANs compared with PD CPNs from the same patient. The finding implies the contribution of pathogenic α-Syn, probably induced by oxidative stress, to selective vulnerability of substantia nigra dopaminergic neurons in human PD.
CRIS-Team Scopus Importer:2020-05-26

Dysfunction of spatacsin leads to axonal pathology in SPG11-linked hereditary spastic paraplegia - Perez-Branguli, Francesc; Mishra, Himanshu Kumar; Prots, Iryna; Havlicek, Steven; Kohl, Zacharias; Saul, Domenica; Rummel, Christine; Dorca-Arevalo, Jonatan; Regensburger, Martin; Graef, Daniela; Sock, Elisabeth; Blasi, Juan; et al. (Human Molecular Genetics, 2014)
Hereditary spastic paraplegias are a group of inherited motor neuron diseases characterized by progressive paraparesis and spasticity. Mutations in the spastic paraplegia gene SPG11, encoding spatacsin, cause an autosomal-recessive disease trait; however, the precise knowledge about the role of spatacsin in neurons is very limited. We for the first time analyzed the expression and function of spatacsin in human forebrain neurons derived from human pluripotent stem cells including lines from two SPG11 patients and two controls. SPG11 patients'-derived neurons exhibited downregulation of specific axonal-related genes, decreased neurite complexity and accumulation of membranous bodies within axonal processes. Altogether, these data point towards axonal pathologies in human neurons with SPG11 mutations. To further corroborate spatacsin function, we investigated human pluripotent stem cell-derived neurons and mouse cortical neurons. In these cells, spatacsin was located in axons and dendrites. It colocalized with cytoskeletal and synaptic vesicle (SV) markers and was present in synaptosomes. Knockdown of spatacsin in mouse cortical neurons evidenced that the loss of function of spatacsin leads to axonal instability by downregulation of acetylated tubulin. Finally, time-lapse assays performed in SPG11 patients'-derived neurons and spatacsin-silenced mouse neurons highlighted a reduction in the anterograde vesicle trafficking indicative of impaired axonal transport. By employing SPG11 patient-derived forebrain neurons and mouse cortical neurons, this study provides the first evidence that SPG11 is implicated in axonal maintenance and cargo trafficking. Understanding the cellular functions of spatacsin will allow deciphering mechanisms of motor cortex dysfunction in autosomal-recessive hereditary spastic paraplegia.
EVALuna2:4956

Gene dosage-dependent rescue of HSP neurite defects in SPG4 patients' neurons - Havlicek, Steven; Kohl, Zacharias; Mishra, Himanshu Kumar; Prots, Iryna; Eberhardt, Esther; Denguir, Naime; Wend, Holger; Ploetz, Sonja; Boyer, Leah; Marchetto, Maria C. N.; Aigner, Stefan; Sticht, Heinrich; et al. (Human Molecular Genetics, 2014)
The hereditary spastic paraplegias (HSPs) are a heterogeneous group of motorneuron diseases characterized by progressive spasticity and paresis of the lower limbs. Mutations in Spastic Gait 4 (SPG4), encoding spastin, are the most frequent cause of HSP. To understand how mutations in SPG4 affect human neurons, we generated human induced pluripotent stem cells (hiPSCs) from fibroblasts of two patients carrying a c.1684C>T nonsense mutation and from two controls. These SPG4 and control hiPSCs were able to differentiate into neurons and glia at comparable efficiency. All known spastin isoforms were reduced in SPG4 neuronal cells. The complexity of SPG4 neurites was decreased, which was paralleled by an imbalance of axonal transport with less retrograde movement. Prominent neurite swellings with disrupted microtubules were present in SPG4 neurons at an ultrastructural level. While some of these swellings contain acetylated and detyrosinated tubulin, these tubulin modifications were unchanged in total cell lysates of SPG4 neurons. Upregulation of another microtubule-severing protein, p60 katanin, may partially compensate for microtubuli dynamics in SPG4 neurons. Overexpression of the M1 or M87 spastin isoforms restored neurite length, branching, numbers of primary neurites and reduced swellings in SPG4 neuronal cells. We conclude that neurite complexity and maintenance in HSP patient-derived neurons are critically sensitive to spastin gene dosage. Our data show that elevation of single spastin isoform levels is sufficient to restore neurite complexity and reduce neurite swellings in patient cells. Furthermore, our human model offers an ideal platform for pharmacological screenings with the goal to restore physiological spastin levels in SPG4 patients.
EVALuna2:2420

GSK3ss-Dependent Dysregulation of Neurodevelopment in SPG11-Patient Induced Pluripotent Stem Cell Model - Mishra, Himanshu Kumar; Prots, Iryna; Havlicek, Steven; Kohl, Zacharias; Pérez-Brangulí, Francesc; Börstler, Tom; Anneser, Lukas; Minakaki, Georgia; Wend, Holger; Hampl, Martin; Leone, Marina; Brückner, Martina; et al. (Annals of Neurology, 2016)
Objective: Mutations in the spastic paraplegia gene 11 (SPG11), encoding spatacsin, cause the most frequent form of autosomal-recessive complex hereditary spastic paraplegia (HSP) and juvenile-onset amyotrophic lateral sclerosis (ALS5). When SPG11 is mutated, patients frequently present with spastic paraparesis, a thin corpus callosum, and cognitive impairment. We previously delineated a neurodegenerative phenotype in neurons of these patients. In the current study, we recapitulated early developmental phenotypes of SPG11 and outlined their cellular and molecular mechanisms in patient-specific induced pluripotent stem cell (iPSC)-derived cortical neural progenitor cells (NPCs).Methods: We generated and characterized iPSC-derived NPCs and neurons from 3 SPG11 patients and 2 age-matched controls.Results: Gene expression profiling of SPG11-NPCs revealed widespread transcriptional alterations in neurodevelopmental pathways. These include changes in cell-cycle, neurogenesis, cortical development pathways, in addition to autophagic deficits. More important, the GSK3ss-signaling pathway was found to be dysregulated in SPG11-NPCs. Impaired proliferation of SPG11-NPCs resulted in a significant diminution in the number of neural cells. The decrease in mitotically active SPG11-NPCs was rescued by GSK3 modulation.Interpretation: This iPSC-derived NPC model provides the first evidence for an early neurodevelopmental phenotype in SPG11, with GSK3ss as a potential novel target to reverse the disease phenotype.

IL-3 receptor signalling suppresses chronic intestinal inflammation by controlling mechanobiology and tissue egress of regulatory T cells. - Ullrich, Karen; Derdau, Julia; Baltes, Carsten; Battistella, Alice; Rosso, Gonzalo; Uderhardt, Stefan; Schulze, Lisa; Liu, Lijuan; Dedden, Mark; Spocinska, Marta; Kainka, Lucina; Kubánková, Markéta; et al. (Gut, 2023)
IL-3 has been reported to be involved in various inflammatory disorders, but its role in inflammatory bowel disease (IBD) has not been addressed so far. Here, we determined IL-3 expression in samples from patients with IBD and studied the impact of Il3 or Il3r deficiency on T cell-dependent experimental colitis. We explored the mechanical, cytoskeletal and migratory properties of Il3r -/- and Il3r +/+ T cells using real-time deformability cytometry, atomic force microscopy, scanning electron microscopy, fluorescence recovery after photobleaching and in vitro and in vivo cell trafficking assays. We observed that, in patients with IBD, the levels of IL-3 in the inflamed mucosa were increased. In vivo, experimental chronic colitis on T cell transfer was exacerbated in the absence of Il-3 or Il-3r signalling. This was attributable to Il-3r signalling-induced changes in kinase phosphorylation and actin cytoskeleton structure, resulting in increased mechanical deformability and enhanced egress of Tregs from the inflamed colon mucosa. Similarly, IL-3 controlled mechanobiology in human Tregs and was associated with increased mucosal Treg abundance in patients with IBD. Collectively, our data reveal that IL-3 signaling exerts an important regulatory role at the interface of biophysical and migratory T cell features in intestinal inflammation and suggest that this might be an interesting target for future intervention.
EVALuna2:539503

Impact of Swiprosin-1/Efhd2 on Adult Hippocampal Neurogenesis - Regensburger, Martin; Prots, Iryna; Reimer, Dorothea; Brachs, Sebastian; Loskarn, Sandra; Lie, Dieter Chichung; Mielenz, Dirk; Winner, Beate (Stem Cell Reports, 2018)
Swiprosin-1/Efhd2 (Efhd2) is highly expressed in the CNS during development and in the adult. EFHD2 is regulated by Ca2+ binding, stabilizes F-actin, and promotes neurite extension. Previous studies indicated a dysregulation of EFHD2 in human Alzheimer's disease brains. We hypothesized a detrimental effect of genetic ablation of Efhd2 on hippocampal integrity and specifically investigated adult hippocampal neurogenesis. Efhd2 was expressed throughout adult neuronal development and in mature neurons. We observed a severe reduction of the survival of adult newborn neurons in Efhd2 knockouts, starting at the early neuroblast stage. Spine formation and dendrite growth of newborn neurons were compromised in full Efhd2 knockouts, but not upon cell-autonomous Efhd2 deletion. Together with our finding of severe hippocampal tauopathy in Efhd2 knockout mice, these data connect Efhd2 to impaired synaptic plasticity as present in Alzheimer's disease and identify a role of Efhd2 in neuronal survival and synaptic integration in the adult hippocampus.
EVALuna2:34019

Increased Th17 cell frequency and poor clinical outcome in rheumatoid arthritis are associated with a genetic variant in the IL4R gene, rs1805010 - Leipe, Jan; Schramm, Markus A.; Prots, Iryna; Schulze-Koops, Hendrik; Skapenko, Alla (Arthritis and Rheumatology, 2014)
The minor allele of the IL4R gene single-nucleotide polymorphism, rs1805010, confers impaired interleukin-4 (IL-4) signaling and has been associated with an aggressive destructive course of rheumatoid arthritis (RA). IL-4 inhibits the development of Th17 cells, a cell population recently identified as being prominent in RA patients and being associated with cartilage and bone destruction. The purpose of the present study was to investigate whether rs1805010 modulates Th17 cell development and, hence, subsequent clinical outcome in RA.A total of 90 patients with early, active RA (mean ± SD Disease Activity Score in 28 joints 4.6 ± 1.1) and 39 control subjects (24 healthy subjects and 15 patients with osteoarthritis [OA]) were genotyped. Serum levels of IL-17 and IL-22 as well as frequencies of Th17 cells were analyzed by enzyme-linked immunosorbent assay and flow cytometry. Clinical and radiographic data were collected and evaluated at baseline and 1 year after disease onset.Twenty-six percent of the RA patients were homozygous for the major allele of rs1805010, 60% were heterozygous, and 14% were homozygous for the minor allele. The RA patients who were homozygous for the minor allele demonstrated significantly higher clinical activity associated with the presence of erosions after 1 year of followup as compared to the other RA patients. The inhibitory effect of IL-4 on Th17 cell development in these patients was significantly less prominent. Accordingly, the frequencies of Th17 cells and serum levels of IL-17 and IL-22 were significantly increased.The data indicate that the rs1805010 minor allele contributes to increased Th17 cell frequency, enhanced clinical activity, and accelerated radiographic progression in RA by rendering CD4 T cells from RA patients insensitive to the attenuating effect of IL-4 on Th17 cell development.
EVALuna2:26224

Infiltrating T lymphocytes reduce myeloid phagocytosis activity in synucleinopathy model - Sommer, Annika; Fadler, Tanja; Dorfmeister, Eva; Hoffmann, Anna-Carin; Xiang, Wei; Winner, Beate; Prots, Iryna (Journal of Neuroinflammation, 2016)
Synucleinopathies comprise a group of neurodegenerative diseases associated with abnormal accumulation of ?-synuclein. One of the key factors that contribute to the progression of synucleinopathies is neuroinflammation. However, the role of lymphocytes in synucleinopathies like Parkinson's disease (PD) remains largely unclear.To investigate how lymphocytes impact synucleinopathies, human wild-type ?-synuclein (WTS) transgenic mice were crossed with mice lacking mature lymphocytes (Rag2(-/-)). In this in vivo model, we quantified ?-synuclein aggregation in the substantia nigra (SN) and striatum and determined the numbers of innate and adaptive immune cells in the central nervous system (CNS). The activation state of resident and infiltrated CNS myeloid cells (M1 vs. M2) was further classified by gene and protein expression analyses. The impact of T and B lymphocytes on the phagocytic activity of microglia in the presence of ?-synuclein aggregates was addressed in BV2 microglia in vitro.Compared to WTS(+) Rag2(+/+) mice, where T but not B lymphocytes infiltrated the CNS, decreased amounts of ?-synuclein aggregates were found in WTS(+) Rag2(-/-) mice devoid of mature lymphocytes. The presence of T lymphocytes did not alter the number of Iba1(+) microglia but increased the frequency of the CD11b(+) CD45(hi) population in the CNS, indicative of an increased number of infiltrated macrophages. Moreover, the M1 phenotype was more prominent in WTS(+) Rag2(+/+) mice, whereas the M2 activation state was dominating in the absence of lymphocytes in WTS(+) Rag2(-/-) mice. In vitro, in the presence of T but not B lymphocytes, significantly less ?-synuclein was phagocytosed by BV2 microglia, further supporting the prevalence of the M1 phenotype in the presence of T lymphocytes.Peripheral T lymphocytes strongly contribute to increased ?-synuclein pathology via modulation of CNS myeloid cell function. In the presence of T lymphocytes, microglia phagocytosis of aggregated ?-synuclein is reduced, which increases the severity of synucleinopathy.
EVALuna2:4741

Interaction of Alpha Synuclein and Microtubule Organization Is Linked to Impaired Neuritic Integrity in Parkinson’s Patient-Derived Neuronal Cells - Schneider, Yanni; Drobny, Alice; Prots, Iryna; Zunke, Friederike; Xiang, Wei; Seebauer, Lukas; Schneider, Yanni; Drobny, Alice; Ploetz, Sonja; Koudelka, Tomas; Tholey, Andreas; Prots, Iryna; et al. (International Journal of Molecular Sciences, 2022)
Parkinson’s disease (PD) is neuropathologically characterized by the loss of dopaminergic neurons and the deposition of aggregated alpha synuclein (aSyn). Mounting evidence suggests that neuritic degeneration precedes neuronal loss in PD. A possible underlying mechanism could be the interference of aSyn with microtubule organization in the neuritic development, as implied by sev-eral studies using cell-free model systems. In this study, we investigate the impact of aSyn on mi-crotubule organization in aSyn overexpressing H4 neuroglioma cells and midbrain dopaminergic neuronal cells (mDANs) generated from PD patient-derived human induced pluripotent stem cells (hiPSCs) carrying an aSyn gene duplication (SNCADupl). An unbiased mass spectrometric analysis reveals a preferential binding of aggregated aSyn conformers to a number of microtubule elements. We confirm the interaction of aSyn with beta tubulin III in H4 and hiPSC-derived mDAN cell model systems, and demonstrate a remarkable redistribution of tubulin isoforms from the soluble to insoluble fraction, accompanied by a significantly increased insoluble aSyn level. Concordantly, SNCA-Dupl mDANs show impaired neuritic phenotypes characterized by perturbations in neurite initiation and outgrowth. In summary, our findings suggest a mechanistic pathway, through which aSyn aggregation interferes with microtubule organization and induces neurite impairments.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Alpha-synuclein; IPSC; Microtubule; Neurite; Neurodegeneration; Parkinson’s disease; SNCA duplication

Intracellular alpha-synuclein affects early maturation of primary oligodendrocyte progenitor cells - Ettle, Benjamin; Reiprich, Simone; Deußer, Janina; Schlachetzki, Johannes; Xiang, Wei; Prots, Iryna; Masliah, Eliezer; Winner, Beate; Wegner, Michael; Winkler, Jürgen (Molecular and Cellular Neuroscience, 2014)
Myelin loss is a widespread neuropathological hallmark of the atypical parkinsonian disorder multiple system atrophy (MSA). On a cellular level, MSA is characterized by alpha-synuclein (aSyn)-positive glial cytoplasmic inclusions (GCIs) within mature oligodendrocytes leading to demyelination as well as axonal and neuronal loss. Oligodendrocyte progenitor cells (OPCs) represent a proliferative cell population distributed throughout the adult mammalian central nervous system. During remyelination, OPCs are recruited to sites of demyelination, differentiate, and finally replace dysfunctional mature oligodendrocytes. However, comprehensive studies investigating OPCs and remyelination processes in MSA are lacking. In the present study, we therefore investigate the effect of human aSyn (h-aSyn) on early primary rat OPC maturation. Upon lentiviral transduction, h-aSyn expressing OPCs exhibit fewer and shorter primary processes at the initiation of differentiation. Until day 4 of a 6day differentiation paradigm, h-aSyn expressing OPCs further show a severely delayed maturation evidenced by reduced myelin gene expression and increased levels of the progenitor marker platelet derived growth factor receptor-alpha (PDGFR?). Matching these results, OPCs that take up extracellular recombinant h-aSyn exhibit a similar delayed differentiation. In both experimental setups however, myelin gene expression is restored at day 6 of differentiation paralleled by decreased intracellular h-aSyn levels indicating a reverse correlation of h-aSyn and the differentiation potential of OPCs. Taken together, these findings suggest a tight link between the intracellular level of h-aSyn and maturation capacity of primary OPCs.
EVALuna2:4696

LRRK2 knockout mice have an intact dopaminergic system but display alterations in exploratory and motor co-ordination behaviors. - Winner, Beate; Prots, Iryna; Hinkle, Kelly M; Yue, Mei; Bahareh, Behrouz; Dächsel, Justus C; Lincoln, Sarah J; Bowles, Erin E; Beevers, Joel E; Dugger, Brittany; Kent, Caroline B; Nishioka, Kenya; et al. (Molecular Neurodegeneration, 2012)
Mutations in the LRRK2 gene are the most common cause of genetic Parkinson's disease. Although the mechanisms behind the pathogenic effects of LRRK2 mutations are still not clear, data emerging from in vitro and in vivo models suggests roles in regulating neuronal polarity, neurotransmission, membrane and cytoskeletal dynamics and protein degradation.We created mice lacking exon 41 that encodes the activation hinge of the kinase domain of LRRK2. We have performed a comprehensive analysis of these mice up to 20 months of age, including evaluation of dopamine storage, release, uptake and synthesis, behavioral testing, dendritic spine and proliferation/neurogenesis analysis.Our results show that the dopaminergic system was not functionally comprised in LRRK2 knockout mice. However, LRRK2 knockout mice displayed abnormal exploratory activity in the open-field test. Moreover, LRRK2 knockout mice stayed longer than their wild type littermates on the accelerated rod during rotarod testing. Finally, we confirm that loss of LRRK2 caused degeneration in the kidney, accompanied by a progressive enhancement of autophagic activity and accumulation of autofluorescent material, but without evidence of biphasic changes.
EVALuna2:26219
Keywords: Parkinson’s disease; Knockout; Dopamine; Microdialysis; Neuropathology; Open-field; Motor co-ordination; Kidney; Autophagy

Modelling human neurodegeneration using induced pluripotent stem cells - Prots, Iryna; Winner, Beate; Winkler, Jürgen (The Matrix of Stem Cell Research. An Approach to Rethinking Science in Society, 2019)
Neurodegeneration is a process of neuronal damage and death. A progressive loss of neurons is a common pathological feature of many neurodegenerative diseases, including motor neuron diseases (MND) and Parkinson's disease (PD). Neurodegenerative diseases are incurable and the only therapies possible are to this date symptomatic. Discovering the mechanisms that either lead to the disease occurrence or that influence the disease progression (together called 'pathomechanisms') would open up possibilities for developing new therapeutic approaches. Cellular material for research in the field of human neurodegeneration is very limited and mostly available as a post-mortem tissue derivate. Therefore, stem cells, as a source of different types of somatic cells, are a very promising tool for developing suitable human models to investigate neurodegeneration. With the discovery of induced pluripotent stem cells (iPSC), researchers now have access to otherwise difficult-to-obtain patient-specific cellular material to investigate the mechanisms that cause neuronal loss and that lead to the development of a neurodegenerative disease. In other words, iPSC-based technology allows the retrieving of disease-specific neurons and thereby allows the observation of the disease development in a dish. In this article, we first describe the symptomatic and current management of two big groups of neurodegenerative diseases: MND and PD. We next explain the advantages of using iPSC technology for the investigation of human neurodegeneration. Then, we highlight a number of pathomechanisms underlying neuronal degeneration in MND and PD, which have been uncovered in iPSC-based models. We finally show that some disease-related phenotypes could already be rescued on a cellular level in the laboratory and discuss the iPSC-based research as a promising tool, fuelling hope that new successful therapies for neurodegenerative disorders can be developed.
CRIS-Team Scopus Importer:2024-08-07
Keywords: Bioscience; Humanities; Medicine; Dentistry; Nursing & Allied Health; Social Sciences

Novel co-culture model of T cells and midbrain organoids for investigating neurodegeneration in Parkinson’s disease - Gerasimova, Elizaveta; Beenen, Amke; Kachkin, Daniil; Regensburger, Martin; Zundler, Sebastian; Blumenthal, David B.; Lutzny-Geier, Gloria; Winner, Beate; Prots, Iryna (npj Parkinson’s Disease, 2025)

NPT100-18A rescues mitochondrial oxidative stress and neuronal degeneration in human iPSC-based Parkinson's model. - Alecu, Julian; Sigutova, Veronika; Brazdis, Razvan Marius; Lörentz, Sandra; Marios-Evangelos, Bogiongko; Nursaitova, Anara; Regensburger, Martin; Roybon, Laurent; Galler, Kerstin Martina; Wrasidlo, Wolfgang; Winner, Beate; Prots, Iryna (BMC Neuroscience, 2025)
BACKGROUND: Parkinson's disease (PD) is a neurodegenerative disorder characterized by protein aggregates mostly consisting of misfolded alpha-synuclein (αSyn). Progressive degeneration of midbrain dopaminergic neurons (mDANs) and nigrostriatal projections results in severe motor symptoms. While the preferential loss of mDANs has not been fully understood yet, the cell type-specific vulnerability has been linked to a unique intracellular milieu, influenced by dopamine metabolism, high demand for mitochondrial activity, and increased level of oxidative stress (OS). These factors have been shown to adversely impact αSyn aggregation. Reciprocally, αSyn aggregates, in particular oligomers, can impair mitochondrial functions and exacerbate OS. Recent drug-discovery studies have identified a series of small molecules, including NPT100-18A, which reduce αSyn oligomerization by preventing misfolding and dimerization. NPT100-18A and structurally similar compounds (such as NPT200-11/UCB0599, currently being assessed in clinical studies) point towards a promising new approach for disease-modification. METHODS: Induced pluripotent stem cell (iPSC)-derived mDANs from PD patients with a monoallelic SNCA locus duplication and unaffected controls were treated with NPT100-18A. αSyn aggregation was evaluated biochemically and reactive oxygen species (ROS) levels were assessed in living mDANs using fluorescent dyes. Adenosine triphosphate (ATP) levels were measured using a luminescence-based assay, and neuronal cell death was evaluated by immunocytochemistry. RESULTS: Compared to controls, patient-derived mDANs exhibited higher cytoplasmic and mitochondrial ROS probe levels, reduced ATP-related signals, and increased activation of caspase-3, reflecting early neuronal cell death. NPT100-18A-treatment rescued cleaved caspase-3 levels to control levels and, importantly, attenuated mitochondrial oxidative stress probe levels in a compartment-specific manner and, at higher concentrations, increased ATP signals. CONCLUSIONS: Our findings demonstrate that NPT100-18A limits neuronal degeneration in a human in vitro model of PD. In addition, we provide first mechanistic insights into how a compartment-specific antioxidant effect in mitochondria might contribute to the neuroprotective effects of NPT100-18A.
EVALuna2:586322
Keywords: iPSC; Dopaminergic neurons; Alpha-synuclein; Aggregation; Parkinson’s disease; Oxidative stress; NPT100-18A; Mitochondria; ROS

Role of α-synuclein in adult neurogenesis and neuronal maturation in the dentate gyrus. - Winner, Beate; Regensburger, Martin; Prots, Iryna; Winkler, Jürgen; et al. (Journal of Neuroscience, 2012)
α-Synuclein has been reported to be important in modulating brain plasticity and to be a key protein in neurodegenerative diseases, including Lewy body dementia (LBD). We investigated how α-synuclein levels modulate adult neurogenesis and the development of dendritic arborization and spines in the dentate gyrus, in which new neurons are constantly added. In the human hippocampus, levels of endogenous α-synuclein were increased in LBD, and the numbers of SOX2-positive cells were decreased. We investigated whether newly generated neurons were modulated by endogenous α-synuclein, and we found increased adult neurogenesis in α/β-synuclein knock-out mice. In contrast, overexpression of human wild-type α-synuclein (WTS) decreased the survival and dendritic development of newborn neurons. Endogenous α-synuclein expression levels increased the negative impact of WTS on dendrite development, suggesting a toxic effect of increasing amounts of α-synuclein. To attempt a rescue of the dendritic phenotype, we administered rolipram to activate the cAMP response element-binding protein pathway, which led to a partial rescue of neurite development. The current work provides novel insights into the role of α-synuclein in adult hippocampal neurogenesis.

Th17 cells: a promising therapeutic target for Parkinson's disease? - Prots, Iryna; Winner, Beate (Expert Opinion on Therapeutic Targets, 2019)
Introduction: Parkinson's disease (PD) is the most common neurodegenerative movement disorder caused by the progressive loss of neurons in the midbrain and other brain regions. Only symptomatic treatment is currently available. Mounting evidence suggests that T cells are a key contributor to PD pathogenesis and neurodegeneration by a mechanism that requires further elucidation. Areas covered: We discuss the evidence of imbalanced activation of effector T cell populations in PD and summarize the data of Th17 involvement and Th17-regulated mechanisms in PD pathology. Moreover, possible Th17-related molecular targets as possible neuroprotective immunomodulatory therapeutic targets for PD are examined. Expert Opinion: Existing data show that Th17 cells, their effector molecules, and signaling pathways are potentially effective therapeutic targets for neuroprotective immunomodulation in PD treatment. However, specificity of action within Th17-mediated signaling pathways for PD requires careful consideration.
CRIS-Team WoS Importer:2019-04-09
Keywords: T cells; Th17 cells; neurodegeneration; Parkinson’s disease; IL-6; IL-1β

Th17 Lymphocytes Induce Neuronal Cell Death in a Human iPSC-Based Model of Parkinson's Disease - Sommer, Annika; Marxreiter, Franz; Krach, Florian; Fadler, Tanja; Grosch, Janina; Maroni, Michele; Gräf, Daniela; Eberhardt, Esther; Riemenschneider, Markus J.; Yeo, Gene W.; Kohl, Zacharias; Xiang, Wei; et al. (Cell Stem Cell, 2019)
EVALuna2:203042

Th17 Lymphocytes Induce Neuronal Cell Death in a Human iPSC-Based Model of Parkinson's Disease - Sommer, Annika; Maxreiter, Franz; Krach, Florian; Fadler, Tanja; Grosch, Janina; Maroni, Michele; Graef, Daniela; Eberhardt, Esther; Riemenschneider, Markus J.; Yeo, Gene W.; Kohl, Zacharias; Xiang, Wei; et al. (Cell Stem Cell, 2018)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by the progressive degeneration of midbrain neurons (MBNs). Recent evidence suggests contribution of the adaptive immune system in PD. Here, we show a role for human T lymphocytes as cell death inducers of induced pluripotent stem cell (iPSC)-derived MBNs in sporadic PD. Higher Th17 frequencies were found in the blood of PD patients and increased numbers of T lymphocytes were detected in postmortem PD brain tissues. We modeled this finding using autologous co-cultures of activated T lymphocytes and iPSC-derived MBNs of sporadic PD patients and controls. After co-culture with T lymphocytes or the addition of IL-17, PD iPSC-derived MBNs underwent increased neuronal death driven by upregulation of IL-17 receptor (IL-17R) and NF kappa B activation. Blockage of IL-17 or IL-17R, or the addition of the FDA-approved anti-IL-17 antibody, secukinumab, rescued the neuronal death. Our findings indicate a critical role for IL-17-producing T lymphocytes in sporadic PD.
EVALuna2:35782

The Ca2+ sensor protein swiprosin-1/EFhd2 is present in neurites and involved in kinesin-mediated transport in neurons - Purohit, Pavitra; Perez-Branguli, Francesc; Prots, Iryna; Borger, Eva; Gunn-Moore, Frank; Welzel, Oliver; Loy, Kristina; Wenzel, Eva Maria; Groemer, Teja W.; Brachs, Sebastian; Holzer, Max; Buslei, Rolf; et al. (PLoS ONE, 2014)
Swiprosin-1/EFhd2 (EFhd2) is a cytoskeletal Ca2+ sensor protein strongly expressed in the brain. It has been shown to interact with mutant tau, which can promote neurodegeneration, but nothing is known about the physiological function of EFhd2 in the nervous system. To elucidate this question, we analyzed EFhd2-/-/lacZ reporter mice and showed that lacZ was strongly expressed in the cortex, the dentate gyrus, the CA1 and CA2 regions of the hippocampus, the thalamus, and the olfactory bulb. Immunohistochemistry and western blotting confirmed this pattern and revealed expression of EFhd2 during neuronal maturation. In cortical neurons, EFhd2 was detected in neurites marked by MAP2 and co-localized with pre- and post-synaptic markers. Approximately one third of EFhd2 associated with a biochemically isolated synaptosome preparation. There, EFhd2 was mostly confined to the cytosolic and plasma membrane fractions. Both synaptic endocytosis and exocytosis in primary hippocampal EFhd2-/- neurons were unaltered but transport of synaptophysin-GFP containing vesicles was enhanced in EFhd2-/- primary hippocampal neurons, and notably, EFhd2 inhibited kinesin mediated microtubule gliding. Therefore, we found that EFhd2 is a neuronal protein that interferes with kinesin-mediated transport.
EVALuna2:7246

The Quest for Anti-α-Synuclein Antibody Specificity—Lessons Learnt From Flow Cytometry Analysis - Leupold, Lukas; Sigutova, Veronika; Gerasimova, Elizaveta; Regensburger, Martin; Zundler, Sebastian; Zunke, Friederike; Xiang, Wei; Winner, Beate; Prots, Iryna (Frontiers in Neurology, 2022)
The accumulation of alpha-synuclein (aSyn) is the hallmark of a group of neurodegenerative conditions termed synucleopathies. Physiological functions of aSyn, including those outside of the CNS, remain elusive. However, a reliable and reproducible evaluation of aSyn protein expression in different cell types and especially in low-expressing cells is impeded by the existence of a huge variety of poorly characterized anti-aSyn antibodies and a lack of a routinely used sensitive detection methods. Here, we developed a robust flow cytometry-based workflow for aSyn detection and antibody validation. We test our workflow using three commercially available antibodies (MJFR1, LB509, and 2A7) in a variety of human cell types, including induced pluripotent stem cells, T lymphocytes, and fibroblasts, and provide a cell- and antibody-specific map for aSyn expression. Strikingly, we demonstrate a previously unobserved unspecificity of the LB509 antibody, while the MJFR1 clone revealed specific aSyn binding however with low sensitivity. On the other hand, we identified an aSyn-specific antibody clone 2A7 with an optimal sensitivity for detecting aSyn in a range of cell types, including those with low aSyn expression. We further utilize our workflow to demonstrate the ability of the 2A7 antibody to distinguish between physiological differences in aSyn expression in neuronal and non-neuronal cells from the cortical organoids, and in neural progenitors and midbrain dopaminergic neurons from healthy controls and in patients with Parkinson's disease who have aSyn gene locus duplication. Our results provide a proof of principle for the use of high-throughput flow cytometry-based analysis of aSyn and highlight the necessity of rigorous aSyn antibody validation to facilitate the research of aSyn physiology and patholog
Keywords: alpha-synuclein; antibodies; synuclein antibodies; T cell; antibody specificity; flow cytometry; α-synuclein expression

The Trojan horse - neuroinflammatory impact of T cells in neurodegenerative diseases - Sommer, Annika; Winner, Beate; Prots, Iryna (Molecular Neurodegeneration, 2017)
Neuronal degeneration is a common mechanism of many neurological diseases including Parkinson's disease (PD), Alzheimer's disease (AD), and Multiple Sclerosis (MS). While AD and PD are classical neurodegenerative diseases, the primary pathology in MS is driven by autoimmune inflammation, attacking oligodendrocytes and thereby inducing neurodegeneration. In AD and PD, immune cells are also considered to play an important role in the disease progression. While the role of local central nervous system (CNS) innate immune cells is well described, a potential influence of adaptive immune cells in PD and AD is not yet fully understood.Here, we aim to summarize findings concerning adaptive immune cells in PD pathogenesis and compare them to AD and MS. In the first part, we focus on disease-specific alterations of lymphocytes in the circulating blood. Subsequently, we describe what is known about CNS-infiltrated lymphocytes and mechanisms of their infiltration. Finally, we summarize published data and try to understand the mechanisms of how lymphocytes contribute to neurodegeneration in PD, AD, and MS.Lymphocytes are critically involved in the pathogenesis of MS, and clarifying the role of lymphocytes in PD and AD pathogenesis might lead to an identification of a common signature of lymphocytes in neurodegeneration and thus pave the road towards novel treatment options.
EVALuna2:34020

Translocation of Distinct Alpha Synuclein Species from the Nucleus to Neuronal Processes during Neuronal Differentiation - Pieger, Katharina; Schmitt, Verena; Gauer, Carina; Gießl, Nadja; Prots, Iryna; Winner, Beate; Winkler, Jürgen; Brandstätter, Johann Helmut; Xiang, Wei (Biomolecules, 2022)
Alpha synuclein (aSyn) and its aggregation are crucial for the neurodegeneration of Parkinson's disease (PD). aSyn was initially described in the nucleus and presynaptic nerve terminals. However, the biology of nuclear aSyn and the link of aSyn between subcellular compartments are less understood. Current knowledge suggests the existence of various aSyn species with distinct structural and biochemical properties. Here, we identified a C-terminal-targeting aSyn antibody (Nu-aSyn-C), which has a high immunoaffinity towards aSyn in the nucleus. Comparing the Nu-aSyn-C antibody to aSyn antibodies developed against phosphorylated or aggregated forms, we observed that nuclear aSyn differs from cytosolic aSyn by an increased phosphorylation and assembly level in proliferating cells. Employing Nu-aSyn-C, we characterized aSyn distribution during neuronal differentiation in midbrain dopaminergic neurons (mDANs) derived from human-induced pluripotent stem cells (hiPSCs) and Lund human mesencephalic cells, and in primary rat hippocampal neurons. We detected a specific translocation pattern of aSyn during neuronal differentiation from the nucleus to the soma and finally to neuronal processes. Interestingly, a remarkable shift of Nu-aSyn-C-positive species towards neurites was detected in hiPSC mDANs from a PD patient carrying aSyn gene duplication. Together, our results reveal distinct nuclear and cytosolic aSyn species that redistribute during neuronal differentiation-a process that is altered in PD-derived neurons.
CRIS-Team WoS Importer:2022-09-09

Unique signatures of stress-induced senescent human astrocytes - Simmnacher, Katrin; Krach, Florian; Schneider, Yanni; Alecu, Julian E.; Mautner, Lena; Klein, Paulina; Roybon, Laurent; Prots, Iryna; Xiang, Wei; Winner, Beate (Experimental Neurology, 2020)
Senescence was recently linked to neurodegeneration and astrocytes are one of the major cell types to turn senescent under neurodegenerative conditions. Senescent astrocytes were detected in Parkinson's disease (PD) patients' brains besides reactive astrocytes, yet the difference between senescent and reactive astrocytes is unclear. We aimed to characterize senescent astrocytes in comparison to reactive astrocytes and investigate differences and similarities. In a cell culture model of human fetal astrocytes, we determined a unique senescent transcriptome distinct from reactive astrocytes, which comprises dysregulated pathways. Both, senescent and reactive human astrocytes activated a proinflammatory pattern. Astrocyte senescence was at least partially depending on active mechanistic-target-of-rapamycin (mTOR) and DNA-damage response signaling, both drivers of senescence. To further investigate how PD and senescence connect to each other, we asked if a PD-linked environmental factor induces senescence and if senescence impairs midbrain neurons. We could show that the PD-linked pesticide rotenone causes astrocyte senescence. We further delineate, that the senescent secretome exaggerates rotenone-induced neurodegeneration in midbrain neurons differentiated from human induced pluripotent stem cells (hiPSC) of PD patients with alpha-synuclein gene (SNCA) locus duplication.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Alpha synuclein; Astrocyte neuron interplay; iPSC derived neurons; Parkinson's disease; Reactive astrocyte; Rotenone; Senescence

α-Synuclein oligomers impair neuronal microtubule-kinesin interplay. - Winner, Beate; Prots, Iryna; Brey, Stefanie; et al. (Journal of Biological Chemistry, 2013)
Early α-synuclein (α-Syn)-induced alterations are neurite pathologies resulting in Lewy neurites. α-Syn oligomers are a toxic species in synucleinopathies and are suspected to cause neuritic pathology. To investigate how α-Syn oligomers may be linked to aberrant neurite pathology, we modeled different stages of α-Syn aggregation in vitro and investigated the interplay of α-Syn aggregates with proteins involved in axonal transport. The interaction of wild type α-Syn (WTS) and α-Syn variants (E57K, A30P, and aSyn(30-110)) with kinesin, tubulin, and the microtubule (MT)-associated proteins, MAP2 and Tau, is stronger for multimers than for monomers. WTS seeds but not α-Syn oligomers significantly and dose-dependently reduced Tau-promoted MT assembly in vitro. In contrast, MT gliding velocity across kinesin-coated surfaces was significantly decreased in the presence of α-Syn oligomers but not WTS seeds or fibrils (aSyn(30-110) multimers). In a human dopaminergic neuronal cell line, mild overexpression of the oligomerizing E57K α-Syn variant significantly impaired neurite network morphology without causing profound cell death. In accordance with these findings, MT stability, neuritic kinesin, and neuritic kinesin-dependent cargoes were significantly reduced by the presence of α-Syn oligomers. In summary, different α-Syn species act divergently on the axonal transport machinery. These findings provide new insights into α-Syn oligomer-driven neuritic pathology as one of the earliest events in synucleinopathies.

α-Synuclein oligomers induce early axonal dysfunction in human iPSC-based models of synucleinopathies - Prots, Iryna; Grosch, Janina; Brazdis, Razvan-Marius; Simmnacher, Katrin; Veber, Vanesa; Havlicek, Steven; Hannappel, Christian; Krach, Florian; Krumbiegel, Mandy; Schuetz, Oliver; Reis, André; Wrasidlo, Wolfgang; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
α-Synuclein (α-Syn) aggregation, proceeding from oligomers to fibrils, is one central hallmark of neurodegeneration in synucleinopathies. α-Syn oligomers are toxic by triggering neurodegenerative processes in in vitro and in vivo models. However, the precise contribution of α-Syn oligomers to neurite pathology in human neurons and the underlying mechanisms remain unclear. Here, we demonstrate the formation of oligomeric α-Syn intermediates and reduced axonal mitochondrial transport in human neurons derived from induced pluripotent stem cells (iPSC) from a Parkinson's disease patient carrying an α-Syn gene duplication. We further show that increased levels of α-Syn oligomers disrupt axonal integrity in human neurons. We apply an α-Syn oligomerization model by expressing α-Syn oligomer-forming mutants (E46K and E57K) and wild-type α-Syn in human iPSC-derived neurons. Pronounced α-Syn oligomerization led to impaired anterograde axonal transport of mitochondria, which can be restored by the inhibition of α-Syn oligomer formation. Furthermore, α-Syn oligomers were associated with a subcellular relocation of transport-regulating proteins Miro1, KLC1, and Tau as well as reduced ATP levels, underlying axonal transport deficits. Consequently, reduced axonal density and structural synaptic degeneration were observed in human neurons in the presence of high levels of α-Syn oligomers. Together, increased dosage of α-Syn resulting in α-Syn oligomerization causes axonal transport disruption and energy deficits, leading to synapse loss in human neurons. This study identifies α-Syn oligomers as the critical species triggering early axonal dysfunction in synucleinopathies.
EVALuna2:34623
Keywords: alpha-synuclein; oligomers; axonal transport; synucleinopathies; neurodegeneration